Electrophysiological correlates of bilateral and unilateral repetitive transcranial magnetic stimulation in patients with bipolar depression. (30th June 2016) - Kazemi, Reza; Rostami, Reza; Khomami, Sanaz; Horacek, Jiri; Brunovsky, Martin; Novak, Tomas; Fitzgerald, Paul B
Abstract: Repetitive transcranial magnetic stimulation (rTMS) has been demonstrated to have efficacy in the treatment of unipolar depression but limited research has explored the efficacy of rTMS in bipolar depression. Therefore, we conducted a comparative clinical trial evaluating clinical responses to prefrontal bilateral and unilateral rTMS in patients suffering from bipolar depression. We hypothesized that, 1) the response to the treatment would be associated with a decrease in the frequency of beta waves, 2) bilateral stimulation of the cortex would bring about more extensive changes in brain activity than unilateral stimulation, and 3) bilateral stimulation is more effective than unilateral. Thirty patients with bipolar depression were divided into two groups. Bilateral Group (n=15) who received rTMS in the left DLPFC (10 Hz) and right DLPFC (1-Hz), and unilateral group (n=15) who received the stimulation only in the right DLPFC (1-Hz) during 20 treatment sessions. The proportion of responders in the bilateral stimulation group was significantly higher than that in the unilateral group [80% versus 47%]. The remission rate was 40% in the bilateral group and 40% in the unilateral group (not significant). In the responders to bilateral rTMS treatment, a significant reduction of alpha1–2, beta 1–3, and gamma frequencies were observed in medial and superior frontal and cingulate gyrus . Responders to the unilateral treatment showed decrease of gamma frequency in postcentral gyrus, precuneus, superior and inferior parietal lobule, Cuneus and angular gyrus. In conclusion, we found that bilateral stimulation was more effective than the unilateral stimulation and evidence that beta frequency activity could possibly be used as a marker for response to rTMS. Highlights: In bilateral stimulation the response rate more than unilateral rTMS. Responders had a remarkable reduction in gamma frequency in unilateral stimulation. Beta coherence can be considered as a marker for response to rTMS.